PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA AJAR INTERAKTIF BERBASIS MISTERI BOKS ANGKA ALJABAR PADA SISWA SMP - Kasmawati; Norma Nasir (Afore : Jurnal Pendidikan Matematika, 2026)
This study aims to explore the effectiveness of the Algebra Number Mystery Box (MBAA) as an interactive, group-based game learning media in enhancing students’ learning motivation and understanding of algebra concepts at the Junior High School level. MBAA is designed as an educational media that combines elements of mystery and challenge in the form of games, thereby encouraging active engagement of students both individually and in groups. The study was conducted through a trial of the learning media with 33 students, collecting data through observations of enthusiasm, learning motivation, social interaction, as well as assessments of algebra concept comprehension before and after using MBAA. The results show that the use of MBAA significantly improves learning motivation, active participation in group activities, and social interaction among students, while creating a more enjoyable and challenging learning experience. Further analysis reveals that the combination of mystery and collaborative elements supports the principles of gamification and constructivist theory, which emphasize active, experience-based learning. In conclusion, MBAA has the potential as an innovative solution to address challenges in mathematics learning, particularly in algebra at the junior high school level. This study recommends further development to enhance accessibility, activity variation, and integration with digital technology to broaden the effectiveness of this learning media in wider educational contexts